Union with the transcendent God in Philo and John"s Gospel - De Villiers, Pieter G. R. (HTS teologiese studies, 2014)
This article analyses the experience of divine presence within an intimate divine-human relationship, as conceptualised in Philo’s writings, and compares this experience with mystical passages in John’s Gospel. The article explains their understanding of God and how the union with a transcendent God is mediated. The article investigates this union in terms of an underlying mystical pattern that existed in the 1st century CE. The pattern explains similarities of Philo’s works with John’s Gospel that indicates the former’s mystical nature. Special attention is given to Philo’s accounts because his own mystical experiences and views are relatively unknown in New Testament scholarship, whilst John’s Gospel is compared to show how this pattern existed within a Jewish-Christian setting. After an introduction to the relevance of mysticism in contemporary research on Philo and John, the article, without trying to establish any genetic link between Philo and John, evaluates the understanding of mystical union in the light of Philo’s own mystical experience and pronouncements. Then follows a discussion of Philo’s understanding of the divine longing for union with humanity despite the divine transcendence, with attention to the direct and indirect manner in which this union is mediated. Finally, similar motifs in John’s Gospel are investigated.